2008
DOI: 10.17221/246/2008-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Relations between polyphenols content and antioxidant activity in vine grapes and leaves

Abstract: The occurrence and content of some polyphenols and the antioxidant activity of compounds present in grape berries, stems and leaves of <i>Vitis vinifera</i> L. were evaluated. Three white and three blue varieties of grapevine were investigated. The contents were determined of <i>trans</i>-resveratrol, <i>trans</i>-piceid, caftaric acid, tryptophan, catechin, epicatechin, total polyphenols, and flavanols, both in healthy material and in the samples of the plant material infes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 20 publications
6
23
0
Order By: Relevance
“…The presence of these compounds was in agreement with previous reports identifying caftaric acid, epicatechin, and quercetin and malvidin derivatives as the main metabolites concerning grape stems [40,41]. Although the presence of stilbenes in grape canes has been reported previously [42][43][44], these compounds were not detected in this study. The absence of stilbenoids in grapevine extracts can be attributed to the use of polar aqueous extraction conditions and the lack of UV-C irradiation in grapevines, as the biosynthesis of resveratrol in grape leaves is strongly increased in response to UV-C irradiation [45], or the storage at −20 • C of grapevine canes after collection.…”
Section: Phenolic Acidssupporting
confidence: 93%
“…The presence of these compounds was in agreement with previous reports identifying caftaric acid, epicatechin, and quercetin and malvidin derivatives as the main metabolites concerning grape stems [40,41]. Although the presence of stilbenes in grape canes has been reported previously [42][43][44], these compounds were not detected in this study. The absence of stilbenoids in grapevine extracts can be attributed to the use of polar aqueous extraction conditions and the lack of UV-C irradiation in grapevines, as the biosynthesis of resveratrol in grape leaves is strongly increased in response to UV-C irradiation [45], or the storage at −20 • C of grapevine canes after collection.…”
Section: Phenolic Acidssupporting
confidence: 93%
“…The DNA extracted from canes and dried leaves were of good quality in all five protocols (Figure 1). In the grapevine samples, all five methods produced better quality DNA from green canes compared to fresh leaves, which was perhaps due to the relatively low content of secondary metabolites and high levels of antioxidants in canes (Balik et al, 2008). However, in most protocols, the concentration of DNA extracted from canes was lower than that obtained from dried leaves ( Table 1).…”
Section: Resultsmentioning
confidence: 97%
“…For the evaluation of the antioxidant activity of vine grapes and wines, several methods were used (Fernández-Pachón et al, 2006;Stratil et al, 2008). Balik et al (2008) reported that grape berries infected by fungal disease showed a higher antioxidant activity, which was most closely correlated with the content of total polyphenols (correlation coefficient = 0.8336-0.9952). Downy mildew, caused by Plasmopara viticola (Berk.…”
Section: Introductionmentioning
confidence: 99%